Late Holocene Climate Changes in the Altai Region Based on a First High‐Resolution Biomarker Isotope Record From Lake Khar Nuur. Issue 20 (19th October 2021) - Bliedtner, Marcel; Struck, Julian; Strobel, Paul; Salazar, Gary; Szidat, Sönke; Bazarradnaa, Enkhtuya; Lloren, Ronald; Dubois, Nathalie; Zech, Roland
Abstract: The Late Holocene marks a substantial cultural and economic transition in the eastern Eurasian Steppe and Altai Region with the dispersal of nomadic pastoralism. So far, paleoclimate conditions during this time remain unclear and controversial. Here, we present a high‐resolution 4.2 ka paleoclimate record from Lake Khar Nuur in the Mongolian Altai that is based on lake sediment proxies and biomarker compound‐specific δ 2 H analyses. Our results document increased aridity before ∼3.7 cal. ka BP, followed by two pronounced phases of warm and wet conditions from ∼3.5–2.8 to ∼2.3–1.5 cal. ka BP, and a strong increase in aridity since ∼1.5 cal. ka BP. Phases of warmer and wetter conditions coincide with a negative North Atlantic Oscillation, which has been responsible for advecting moisture into the region by more southerly‐displaced Westerlies and possibly favored the expansion of mobile nomadic pastoralism in the region. Plain Language Summary: Nomadic pastoralism is the dominant subsistence practice in the eastern Eurasian Steppe and Altai Region since the Late Bronze Age. Whether this had climatic reasons is one of the most intriguing question, because former climatic conditions are poorly understood in this important but understudied region. To address this issue, we established a hydrological record for the last ∼4.2 ka from a high‐altitude lake in the Mongolian Altai. Our findings provide evidence of exceptionally warm and wet conditions from ∼3.5–2.8 and ∼2.3–1.5 cal. ka BP. Those favorable climate conditions likely favored productive grasslands and the widespread dispersal of nomadic pastoralism in the eastern Eurasian Steppe and Altai Region. Key Points: A high‐resolution 4.2 ka paleoclimate record from Lake Khar Nuur in the Mongolian Altai, based on biomarker compound‐specific δ 2 H analyses Our hydrological proxies record distinct changes in warm/wet and cold/dry conditions during the Late Holocene in the Altai Region Pronounced warm/wet conditions from ∼3.5 to 2.8 cal. ka BP probably favored the widespread dispersal of nomadic pastoralism in the region